MORPHOLOGICAL STUDY OF THE COMBINED LASER AND PHOTODYNAMIC EFFECT WITH RADACHLORIN ON THE STRUCTURE OF EXPERIMENTAL EHRLICH SARCOMA - Rostovtsev, Nikolay; Zhukovskaya, Elena; Pasternak, Alexey; Kotlyarov, Alexander (Revista Inclusiones, 2020)
The relevance of the problem studied is due to the social importance of introduction of highly effective methods of malignant tumors treatment. The article analyzes processing methods of laser radiation used and its antineoplastic activity. The experimental method of radochlorin effect on the Ehrlich sarcoma laboratory model was used as a basic method for the study of this problem. The main results of the research are fundamental and describe new, previously unknown aspects of intraoperative photodynamic therapy (using radachlorin) combined with high-intense laser radiation and its effect on Ehrlich sarcoma tumor tissue. Laser photodynamic therapy (PDT) was followed not only by typical circulatory disturbance, but also by suppressed growth factor expression of tumor angiogenesis. Captose-3-dependent apoptosis was proved activate under the influence of photosensitizer of the second generation. Apoptotic index significantly increases during the first week after laser PDT session in a dose of 200-400 J/cm2 , and laser PDT dose increase results in the lower expression of blc-2 oncoprotein and tumor cell proliferative activity at all stages of the experiment. The results of the study may be of great importance in developing new clinical methods for intraoperative laser radiation effect in treatment of malignant tumors.